Non-English Majored Learners' Perception, Expectation and Difficulties Towards ELT Classroom - Zuliana Lestari Zulkarnain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
English proficiency has been difficult to achieve by non-English majored learners, yet it is important that they be good at it in order to compete in their work field. This study investigated learners’ perception towards English, and their expectation, perception, and difficulties in ELT classroom. This research was descriptive qualitative research which involved one lecturer and 16 first semester students of a non-English majored tertiary education. The data were obtained through questionnaire and interview. The results pointed out that the learners had positive perception towards English and their ELT classroom. It was expected that English subject be learned in more than one semester and English be used as the dominant medium of instructions. Due to lack of vocabulary and pronunciation, speaking was chosen as the major difficulty by the learners. Keywords: Difficulty, ELT Classroom Perception, Expectation.